The Influence of Opinion Leaders on the Decisions of Online Gamblers - Pedreño Santos, Ana; Viñarás Abad, Mónica; Carcelen García, Sonia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In the context of online gambling, opinion leaders play a key role in promoting the platforms. These opinion leaders include influencers, sports experts, tipsters, streamers, professional players and public figures. This paper identifies the characteristics of opinion leaders in terms of their impact on young players. The methodology applied consists of a digital community in which the participants, young gamblers, share their opinions on the marketing strategies carried out by the bookmakers. The results show how the presence of other players or influencers has a persuasive capacity superior to other strategies